The mediating role of food safety in the relationship between halal perception, perceived quality, and purchase decisions: evidence from muslim university students in indonesia and malaysia - Roisu Eny Mudawaroch; Isna Windani; Jeki Mediantari Wahyu Wibawanti; Faruq Iskandar; Zulfanita; Rinawidiastuti; Nor Hidayatun Abdul Razak; Yusnita Wahyuni Silitonga (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2025)
This study examines the structural relationships among halal perception, food safety, perceived product quality, and purchase decisions for halal food products, with food safety positioned as a mediating construct. Grounded in consumer perception theory and the halal–thayyib framework, the study conceptualizes halal as a credence attribute that shapes perceived safety and, subsequently, quality evaluation. A cross-sectional survey was conducted among Muslim university students in Indonesia and Malaysia, and the data were analyzed using covariance-based Structural Equation Modeling (CB-SEM) to test the proposed causal model. The results indicate that halal perception significantly influences perceived food safety, which in turn positively affects perceived quality and purchase decisions. However, halal perception does not directly influence perceived quality, suggesting that consumers interpret halal primarily through a safety lens rather than as an intrinsic quality cue. These findings highlight the mediating role of food safety in translating religious compliance into market-relevant product evaluations. The study contributes theoretically by clarifying the perceptual mechanism linking halal attributes to consumer decisions and offers practical implications for halal certification bodies and food producers in strengthening safety communication strategies.